Métodos de siembra y su influencia en la incidencia de malezas en el cultivo de arroz (Oryza sativa L.) en la zona de Babahoyo - Jiménez Bayas, Angel Aníbal (2017)
SUMMARY This experimental work was carried out on the premises of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at km 7 ½ via Babahoyo - Montalvo, with geographical coordinates 790 32` west longitude and 10 49` south latitude and A height of 8 masl. The soil is clay loam, average annual temperature of 25.5 ° C, mean annual rainfall of 2203.8 mm and relative humidity of 79.6%. Seeds of the variety INIAP 14 were used as seed material. Two factors were studied as treatments. Factor A: sowing methods (direct and transplant) and Factor B (Mixtures and doses of herbicides / ha) as: Grammya (150 cc) + Executioner (100 cc); Grammya (200) + Executioner (150); Grammya (250) + Pamex (350) + Amine (100); The experimental design of Completely Randomized Blocks was used in factorial arrangement A x B, where Factor A represents the methods of sowing, the Factor B mixtures of the herbicides with their respective doses and three replicates. Comparison of the averages was evaluated using the Tukey test at 5% probability. During the development of the crop, soil analysis, soil preparation, sowing, irrigation, fertilization, weed control, phytosanitary control and harvesting were carried out. The data evaluated were toxicity index at 7 and 14 days after application of the products, weed control at 15 and 30 days after application of herbicides, plant height, number of tillers and panicles / m2, Panicle length, grain per spike, grain - straw ratio, weight of 1000 grains, ratio of full and bare grains, yield and economic analysis. From the results, it was determined that there was influence among the sowing methods and the incidence of weeds in rice cultivation in the Babahoyo area; Treatment toxicity was reported with Grammya (300) + Pamex (400) + Amine (150) with 0.7 equivalent to little damage at 7 days after application of the products, disappearing at 14 days; The best weed control was obtained Grammya (150 cc) + Verdugo (100 cc) and Grammya (250) + Pamex (350) + Amine (100), the blends of the product being referred to as excellent or very good; The planting method by Grammya (300) + Pamex (400) + Amina (150) obtained higher plant height, while direct sowing with Grammya (250) + Pamex (350) + Amina (100) Panicle length; The direct sowing with the use of Grammya (150 cc) + Verdugo (100 cc) and Grammya (200) + Verdugo (150) registered more tillers / m2 and sowing by transplant with Grammya (300) + Pamex (400) + Amine (150) stood out in terms of panicles / m2; The highest number of grains per spike was achieved by the grafting method applying Grammya (150 cc) + Verdugo (100 cc) and no significant differences were obtained in the grain - straw ratio; The direct sowing method applying Grammya (150 cc) + Executioner (100 cc) reported higher number of full grains and the absolute control with the transplant method greater number of vain grains; (300) + Pamex (400) + Amine (150) reached the highest average and the Grammya (200) + Executioner (150) method had the highest yield With 4091.5 kg / ha and the highest net benefit was obtained with the application of Grammya (300) + Pamex (400) + Amina (150) with the direct sowing method with $ 547,92.